Gender, climate change and REDD+ in the Congo Basin forests of Central Africa - Brown, H.C.P. (2011)
The Congo Basin region of Central Africa contains the second largest contiguous tropical rainforest in the world, which is an important source of livelihood for millions of people. It is also important for climate change adaptation, as well as mitigation policies on Reducing Emissions from Deforestation and Forest Degradation (REDD+). Men and women relate to and use the forest differently and so may experience the effects of climate change and REDD+ policies differently. Investigations through semi-structured interviews and document reviews in three countries of the region revealed that women have had limited participation in discussions on issues of climate change or REDD+. There is some evidence that gender consideration will become part of future national REDD+ strategies. Strategies to foster the effective participation of all stakeholders are essential to ensure that gender dimensions are addressed in issues of climate change, forest access, forest management and distribution of carbon benefits.